Effects of work-family; family-work conflicts, self-construal, perceived managerial support and stress on employees’ self-rated performance - Ercan, Safiye Neslihan (My University, 2009)
Work and family are two important realms in people’s lives. Work-family conflict (WFC) and family-work conflict (FWC) refer to the conflicts transferred from work to family and from family to work, respectively. Research shows that WFC and FWC lead to an increase in stress level and there are studies showing that stress causes a decrease in the performance level of employees. In addition, managerial support, which is an important variable in the literature of WFC and FWC, is studied as an independent variable or an intervening variable or a moderating variable. Independent self-construal and interdependent self-construal are important variables of cultural and social psychological studies. The present study aimed to examine the effects of WFC, FWC, self-construals, stress and perceived managerial support on the perception of performance of white-collar employees. One hundred seventy seven participants (73 males and 104 females), who work in the sectors of education, finance and health, filled out a questionnaire that consisted of demographic information and six scales concerning WFC/ FWC, self-construals, stress, perceived managerial support, perceived performance and social desirability. Stress was not found to be an intervening variable between WFC/ FWC and perceived performance. Independent self-construal was found to be a moderating variable between WFC and stress, whereas interdependent self-construal was not found to be a moderating variable between FWC and stress. Perceived managerial support was not found to be a moderating variable between WFC/ FWC and stress, but it was found to be a moderating variable between stress and perceived contextual (extra-role) and general performance. The reasons of these findings were discussed, and additional research questions regarding the relationships between gender and stress, gender and WFC/ FWC, and sector and WFC/ FWC were also tested and explained.

İş ve aile, insanların yaşantısındaki iki önemli alandır. İş-aile çatışması ve aile-iş çatışması, sırasıyla, işten aileye ve aileden işe aktarılan çatışmalardır. Araştırmalar, iş-aile ve aile-iş çatışmalarının, stres seviyesinde artışa sebep olduğunu göstermiştir ve stresin çalışanların performans seviyesinde düşüşe sebep olduğunu gösteren çalışmalar vardır. Ayrıca iş-aile ve aile-iş çatışmaları literatüründe önemli bir değişken olan, yönetici desteği, bağımsız değişken veya ara değişken veya şartlı değişken olarak çalışılmaktadır. Bağımsız benlik tanımı ve karşılıklı bağımlı benlik tanımı, kültür ve sosyal psikoloji çalışmalarının önemli değişkenleridir. Çalışmanın amacı; iş-aile çatışması, aile-iş çatışması, benlik tanımları, stres ve algılanan yönetici desteğinin, beyaz yakalı çalışanların performans algısına etkilerini bulmaktır. Eğitim, finans ve sağlık sektörlerinde çalışan, 177 katılımcı (73 erkek ve 104 kadın), demografik bilgi formu ve iş-aile/ aile iş çatışmaları, benlik tanımları, stres, yönetici desteği algısı, performans algısı ve sosyal beğenilirlik ile ilgili altı ölçekten oluşan bir soru formunu doldurmuşlardır. Stres, iş-aile/ aile-iş çatışmalarıyla performans algısı arasında ara değişken olarak bulunamamıştır. Bağımsız benlik tanımı, iş-aile çatışması ile stres arasında şartlı değişken olarak bulunmuş, öte yandan karşılıklı bağımlı benlik tanımı, aile-iş çatışması ile stres arasında şartlı değişken olarak bulunamamıştır. Yönetici desteği algısı, iş-aile/ aile-iş çatışmalarıyla stres arasında şartlı değişken olarak bulunamamış, ama stres ile çevre bağımlı performans algısı/ genel performans algısı arasında şartlı değişken olduğu bulunmuştur. Bu bulguların sebepleri tartışılmıştır ve cinsiyet ve stres, cinsiyet ve iş-aile/ aile-iş çatışmaları, sektör ve iş-aile/ aile-iş çatışmaları ilişkileri ile ilgili ek araştırma soruları test edilmiş ve açıklanmıştır.
Keywords: Benlik Tanımı; Performans Algısı; Stres